Optimization of Mulberry Extract Foam-Mat Drying Process Parameters - Nguyen Minh Thuy; Vo Quoc Tien; Nguyen Ngoc Tuyen; Tran Ngoc Giau; Vo Quang Minh; Ngo Van Tai (My University, 2022)
Mulberry powder was created from the extract using a foam-mat drying process. The studies aimed to evaluate the effects of egg albumin, carboxymethyl cellulose (CMC), digestion-resistant maltodextrin (DRM) contents, and whipping time (5 to 15 min) on the foam properties. The impact of different drying temperatures (60 to 75 °C) on the quality of the finished mulberry powder was also noted. The best foam expansion/stability value was determined using multiple regression models as a function of egg albumin, CMC, DRM, and whipping time. The results indicated that the main influencing factors for the foam properties were whipping time followed by egg albumin, CMC, and DRM. Optimum values of foam expansion and stability were achieved at 467.9% and 97.02%, respectively. The foam had a porous structure and good stability for subsequent drying, with optimal contents of egg albumin, CMC, and DRM used at 7.6%, 0.4%, and 2%, respectively, along with a whipping time of 14.5 min. The established models had a high coefficient of determination (R2 > 0.9) and a high correlation between the predicted and observed values. Therefore, the model could be adjusted to determine the characteristics of the foam suitable for subsequent drying. The optimal values were then also verified. Minimal fluctuations (1.78−2.98%) between the experimental data and the optimal value were found. The drying temperature also significantly affected the quality of the mulberry powder. The foam was dried at 65 °C for 4 h to produce apowder with a beautiful light color (L* = 62.65), a characteristic purple-red color of mulberry (a* = 5.97). The moisture, water activity, and anthocyanin content of the finished mulberry powder were 4.57%, 0.3, and 5.4 mg/g, respectively.
Keywords: Carboxymethyl cellulose; Maltodextrin; Egg albumin; Microencapsulation and Drying Processes